AFP IN PERU INCURRED USE MISLEADING ADVERTISING AND MISINFORMATION WHEN IT BEGAN OPERATIONS, WHICH BOASTS SWINDLE - Barreda Guerra, Juan Manuel (2015)
The research aims to demonstrate that in the 90s in our country, time in which the ONP SNP was again in financial and economic peak time, so that the financial allocation for pension of pensioners receiving retirement at the time was far from being able to attend and cover not even 40% of basic food to survive. however in 1993 in a government dictatorial and unconstitutional court start is given by Decree Law No. 25897 to the new private pension system, system whereby the Administrators of Pension Funds, private entities created whose primeval business mission was to capture as much of retirees them leave the state system so that, on good account enroll and taper into a particular Administrator of Pension Funds, in order to transfer the registered together with a recognition bond in soles that It would be recognized by the ONP for their contributions made whenever these contributions reached 48 consecutive installments which may assess any of the periods established for the years 1992, 1996, 2001 for the processing of your bonus award, pecuniary amount the new member state grant to AFP in which he inscribed the affiliate, in order that it constitute a savings fund in their individual account as a contributor (Worker saver) in the new pension system. This was under the offer, the worker who saved more than two or three decades, the system had to offer through their advertising messages, a level of “pension” that would allow him to live during your retirement years labor market with sufficient decorum, dignity and comfort that the pension system is not state would never allow it. Today, more than twenty years of operation of the system AFPS, the workers are with plenty of situations and conditions of misinformation at the time of registration over twenty years ago were not given them by the AFPs, which is practice disinformation and misleading advertising in relation to non-compliance with the promises offered in the advertising campaign launch in some cases were joined without signing affiliate agreement. Today workers can see that, everything offered twenty-two years ago, is not true. One of the most critical of the establishment of the private pension system issues has been that the law establishing SSP was given in an unconstitutional and dictatorial government, with which the new model of management of pension funds and imposed State fails to meet international conventions and agreements on its commitment to ensuring the existence and status and continuity of a public pension system. Under this reality, the concept and principle of working welfare state is not fulfilled in million workers in Peru.